Myocardial infarction related to valve replacement surgery. Issue 6 (June 1984) - McGregor, C G; MacLeod, M D; Muir, A L; Smith, A F; Hannan, W J; Miller, H C
Abstract : Fifty consecutive patients, 25 undergoing aortic valve replacement and 25 mitral valve replacement, were studied by serial electrocardiography, preoperative and postoperative technetium-99m pyrophosphate radionuclide scanning, and serial measurement of enzymes (creatine kinase, aspartate aminotransferase, urea stable lactic dehydrogenase) and the MB isoenzyme of creatine kinase to define the incidence of preoperative myocardial infarction and to identify the most appropriate diagnostic techniques. The use of myocardial scanning and measurement of peak enzyme activity proved to be accurate indicators of myocardial infarction, but the electrocardiogram was of limited value. The measurement of creatine kinase MB isoenzyme had no diagnostic advantage over that of the other enzymes. There were two deaths in the series, one due to acute pancreatitis after aortic valve replacement and the other due to myocardial injury after mitral valve replacement. There were four non-fatal myocardial infarctions after aortic valve replacement, giving an incidence of 16%, and none after mitral valve replacement, giving an incidence of 4%.